HUBUNGAN ASUPAN ZAT BESI, ASUPAN SENG DAN STATUS GIZI (IMT/U) DENGAN PRESTASI BELAJAR PADA REMAJA DI SMA IT DAARUL RAHMAN III TAHUN 2020 - Radhwa Aulia Azzahra (2020)
Adolescents are residents ranging from ages 10 - 19 who still in school. The average results of national exam achievement at SMA IT Daarul Rahman III on subjects Indonesian, Mathematics and English were still lower than the national average. The lack of academic achievement can be influenced by nutritional intake, such as intake of iron and zinc. The purpose of this research is to understand the relationship of iron consumption, zinc consumption and nutritional status (IMT/U) with academic achievement of adolescents in SMA IT Daarul Rahman III in 2020. This research is an observational study with cross sectional design. The samples in this research are students of SMA IT Daarul Rahman III with a total of 70 respondents whose taken by simple random sampling method. The relationship between variables were analyzed using Pearson correlation statistical test. The result of univariate test showed that academic achievement of students included in high category (51,4%). The results of bivariate test showed that there are no relationship of iron consumption (p value 0,606), zinc consumption (p value 0,832) and nutritional status (IMT/U) (p value 0,128) with academic achievement. It is recommended to school to provide a quality and quantity of food so that students's intake of nutrients fulfilled and provide health services for students.